ANALISIS PELAKSANAAN SUPERVISI PENDIDIKAN DI SEKOLAH SMA NEGRI 1 PERCUT SEI TUAN: PERSEPEKTIF GURU DAN SISWA (Sindoro: Cendikia Pendidikan, 2025)
This study analyzes the implementation of educational supervision at SMA Negeri 1 Percut Sei Tuan from the perspectives of teachers and students. Educational supervision plays a crucial role in improving the quality of teaching and learning. According to the 2007 Ministry of Education decree, a principal’s competencies include supervisory skills to improve teacher performance.This descriptive study involved teachers and students as respondents, using questionnaires and interviews. The results indicate that most teachers consider supervision helpful for coordinating school efforts and improving teaching skills (in line with the supervisory functions), although more frequent and open communication is needed. Students generally lack detailed understanding of supervision activities but perceive its positive effects through more innovative teaching. In conclusion, supervision at this school should be enhanced by adhering to scientific and collaborative principles, and by providing constructive feedback to teachers.